2004
DOI: 10.1016/j.cardiores.2004.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of early atherosclerosis in LDL-receptor deficient mice by oral tolerance with $beta;2-glycoprotein I

Abstract: Thus, oral administration of beta 2GPI is an effective means of suppressing atherogenesis in mice and should further be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 29 publications
5
25
0
Order By: Relevance
“…In preclinical models, nasal or oral administration of HSP65 reduced atherosclerosis in Ldlr -/-mice (146,147). Similar findings are reported for nasal administration of oxLDL (148,149) or β2-glycoprotein I (150). Another approach is to deliver the relevant antigens via tolerogenic DCs that have suppressed costimulatory functions but maintain antigen-presenting functions.…”
Section: Regulation Of Proatherogenic Adaptive Immune Responsessupporting
confidence: 58%
“…In preclinical models, nasal or oral administration of HSP65 reduced atherosclerosis in Ldlr -/-mice (146,147). Similar findings are reported for nasal administration of oxLDL (148,149) or β2-glycoprotein I (150). Another approach is to deliver the relevant antigens via tolerogenic DCs that have suppressed costimulatory functions but maintain antigen-presenting functions.…”
Section: Regulation Of Proatherogenic Adaptive Immune Responsessupporting
confidence: 58%
“…In previous studies, intranasal inoculation with HSP65 or an apolipoprotein B-100 peptide or oral feeding with ␤2-glycoprotin I resulted in some degree of amelioration of atherosclerosis that correlated with indications of increased IL-10 expression (9,(12)(13)(14). However, none of these studies demonstrated a causative role for IL-10 in the induction of immune tolerance.…”
Section: Discussionmentioning
confidence: 94%
“…Targets for tolerance induction have included ox-LDL (with decreased atherosclerosis after an oral tolerance protocol), malondialdehyde treated LDL (no effect) (1859), HSP60 (reduced atherosclerosis) (1860), HSP65 (reduced atherosclerosis) (1142), and ␤2-glycoprotein I (reduced atherosclerosis) (606) in addition to the APOB-100 studies above. In addition to these "self" targets which had been hypothesized to be involved in the atherogenic sensitization of Th1 cells, mucosal tolerance protocols directed against pneumococcus, or even measles virus envelope resulted in reduced atherosclerosis, suggesting there may be multiple, unsuspected potential antigenic targets as well the possibility of nonspecific effects from simply increasing Treg numbers with increased secretion of IL-10 (30, 241).…”
Section: Evidence For the Atheroprotective Effects Of Tregmentioning
confidence: 99%